Implementing logistics technologies to optimize road transport flows: Urban planning, traffic capacity, and safety - Sarkisian, Hor; Zinevych, Oleksandr; Molyboha, Ruslan; Dubytskyi, Oleksandr; Pavliuk, Vasyl (Edelweiss Applied Science and Technology, 2025)
The relevance of the research topic is driven by contemporary challenges of urbanization and the increasing number of vehicles, which necessitate effective management of transport flows and enhancement of road traffic safety. Implementing logistics technologies, such as Intelligent Transport Systems (ITS) and Geographic Information Systems (GIS), is becoming a priority for optimizing urban transport infrastructure. The research aims to analyze and assess the implementation of logistics technologies for optimizing transport flows in road transport, with the transport system of cities being the research object. The methodological basis of the research is a systems analysis, including theoretical substantiation and practical assessment of the efficiency of using ITS and GIS. The research showed that ITS reduces congestion and increases road capacity through adaptive traffic management and real-time monitoring. Implementing GIS allows for more precise planning and management of transport infrastructure, reducing traffic jams and improving road safety. The practical significance of the results lies in the possibility of their application for improving urban planning, saving time and resources, and enhancing road safety. The analysis showed that successful implementation of logistics technologies requires consideration of technical, organizational, and social aspects, as well as continuous data updating and staff training. Prospects for further research include integrating new technologies and methods to enhance the efficiency of transport systems management and improve the overall transport situation in cities.